Fourier-transform rheology of unvulcanized styrene butadiene rubber filled with increasingly silanized silica. Issue 3 (3rd July 2019) - Nie, Shouliang; Lacayo-Pineda, Jorge; Wilhelm, Manfred
ABSTRACT: Silica as one the most important fillers for rubber material is routinely modified by silane to improve its compatibility with the rubber matrix. Silanization of the silica particle affects both the linear and nonlinear rheological behaviors of the compounds. Their rheological nonlinearity, however, is mostly analyzed in an indirect way from linear rheological parameters, e.g. G′ ( ω 1, γ 0 ) and G ″( ω 1, γ 0 ), which lose their physical meaning in the nonlinear viscoelastic regime. In the present work, the nonlinearity is directly quantified by the Fourier-transform rheology (FT-Rheology) technique in terms of I 3/1 ( ω 1, γ 0 ), the third relative higher harmonic, for unvulcanized styrene butadiene rubber compounds filled with a fixed amount of silica, but varying dosages of silane. With the proposed model for I 3/1 ( γ 0 ), the contributions toward nonlinearity from the filler networks at a low strain amplitude and the one from the polymer networks at high strain amplitude can be successfully separated for filled systems. The utmost nonlinearity contribution from the filler networks decreases with the silane content, which is assigned to the weakening interparticle interaction of the filler. With increasing silanization of silica, the utmost nonlinearity contribution from the polymer networks is found to increase. This nonlinear mechanical response is attributed to the enhanced interfacial interaction between the filler and polymer.